Notation publications in the context of musical life in Lithuania in the XVI-XVII centuries - Trilupaitienė, Jūratė (Knygotyra, 2024)
In the 16th and 17th centuries, musical notation was only a modest part of the published output in Lithuania. What was new in the large centers of music in Western Europe spread here and was incorporated into this country’s musical life, but due to specific political and cultural factors, this did not ensure an even musical development. Lithuania had no long-standing tradition of sponsorship by patrons of the arts, and the publication of notated music was limited to religious purposes and thus highlighted the main musical accents in Lithuanian church music. That a Gregorian chant hymnal was not published until the very middle of the 17th century was largely due to the fact that the Lithuanian Catholic Church was answerable to higher authorities in Poland, which supplied them with most of the liturgical printed material they needed. In the first half of the 17th century, when the Counter-Reformation in Lithuania ended, the Jesuit Academy of Vilnius (founded 1579) began to concern itself with the teaching of Gregorian chant. The Lithuanian Jesuits, now no longer accountable to the Polish church hierarchy, began to make independent decisions about the publication of hymnals. The first Gregorian chant books published in Lithuania by the Vilnius Academy in 1667 were prepared and organized by the Academy’s noted rhetorician, Professor Žygimantas Lauxmin. They were Ars et praxis musica, Graduale, and Antiphonale. These were reprinted till the end of the century, although their polygraphic quality was not particularly high. The chants themselves were recorded in a variety of ways—as cantus planus (plainsong) and cantus fractus—and in mensural (measured) notation. A variant, local to Vilnius, was the printing of the Rorate advent hymn cycle in two-voice parts and several Latin Mass hymns in three parts. It was the Jesuits who published the first Catholic hymnals in Lithuania in 1613, entitled Parthenomelica and prepared by Valentin Bartoszewski. They revealed the formation of a local hymn repertoire and the variability and great flexibility of the hymn melodies, some hymns having only empty staves provided. In the middle of the 16th century, with the Reformation well-established, the printing of Protestant hymnals began with Martynas Mažvydas’ Katekizmas (Catechism). This first Lithuanian book, published in 1547 in Karaliaučius (Koenigsberg), had ten notated hymns. The melodies of some were identical to those in hymnals printed in the Grand Duchy of Lithuania, perhaps because they had sprung from the same source. Lithuania Major’s first notated publications were prepared at the Vilnius court of Mikołaj Radvila the Black, printed on his presses in 1558 in Brest and entitled Pieśni chwały Bożych. They were a collection of single and multiple-voice hymns. The music was composed in Vilnius by Wenceslaus Schamotulinus and Ciprianus Basilicus, who were in Radvila’s employ. Later Protestant hymnals with notation were published in 1563-4 in Nesvyžius, and in 1580, 1581, 1594, 1598, and 1600 in Vilnius, and in 1614 and 1620 in Lubcza. It is thought that the impetus and backing of Radvila the Black as patron of the first Protestant hymnal led to the publication of his court composers’ work outside the borders of the Grand Duchy of Lithuania, as was done in Cracow in the middle of the century. The distinct decrease in the printing of hymns scored for many voice parts after Radvila’s death in 1565 confirms his influence. It may also be that Radvila financed the 1565 Cracow publication of the tabulature of Valentin Bakfark (Bacfark) living in Vilnius. Furthermore, Radvila’s death marked the end of Basilicus’ career as a composer and the sudden disappearance of Bacfark from Vilnius. The greater part of books published in Vilnius in 1598 (M. Petkevičius’ Katekizmas) and in Kėdainiai (Knygos nobažnystės krikščioniškos in 1653) were hymnals whose hymns were based on melodies from the above-mentioned Vilnius publications. The publication of notated music in the 16th-17th centuries was limited to Protestant and Catholic hymnals, which provide valuable information about Lithuanian church music and about the cultural climate of that period in general.